Willingness to Pay dan Karakteristik Konsumen Daging Ayam Halal Berdasarkan Pendekatan Pasar Hipotetik: Willingness to Pay and Consumer Characteristics of Halal Chicken Based on a Hypothetical Market Approach - Muhammad Basir Paly (Anoa: Journal of Animal Husbandry, 2022)
This study aims to (1) determine the amount of Willingness to Pay (WTP) for halal chicken meat (DA), and (2) the characteristics of halal chicken consumers who are willing to pay the WTP price. A total of 50 halal chicken consumers taken from 2 traditional markets were interviewed as respondents. To determine WTP, a hypothetical market approach is used with the Continget Valuation Method (CVM). WTP prices are divided into two categories; WTP0 corresponds to the market price, and WTP1 increases 5% above the market price. Data were analyzed by descriptive statistics, and variable logistic regression. The results showed that 85.35% of consumers were willing to pay a 5% price increase, while 14.65% were not. With this 5% price increase, halal chicken suppliers get an additional sales turnover of IDR 16.8 million per month or 201.6 million per year. Characteristics of respondents who determine WTP are education level, household income, and consumer awareness of halal products. The study concluded that the halal WTP allows suppliers to build small-scale halal slaughterhouses (200-300 heads) per day